Study of surface roughness effects to liquid contact angle on solid surface - Mohd Shahrir Ashraf, Abdul Wahab (2016)
This thesis deals with measurement of liquid contact angle with different surface roughness. The objective of this thesis is to measure the contact angle on different material of solid surfaces and to measure the effect of surface roughness to the shape of liquid drop from above view. Sessile drop method is used in this paper to determine the contact angle and drop shape of a liquid. The result is trustful and easy to apply. With this method, the intersection of three interface line and contact angle that state in Young’s equation can be achieved. This method also has been shown to improve the contact angle measurement. The material used is mild steel with four different roughness, 0.321μm, 0.635μm, 2.325μm and 3.353μm. The surface roughness is very important to determine the contact angle. The increase the roughness of the surface, the larger the contact angle meanwhile the wetting properties become lower. As a result, liquid contact angle increased with increasing plate surface roughness and liquid dropped on higher roughness presents smaller diameter with more edge curve.